A Study on Demonstration of the Nature of Science in Science Textbooks: History and Philosophy of Science Perspectives - AyÄ±k, Z.; CoÅŸtu, B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
Many scholars in the teaching of science put forth that the perennial target of science education is to teach the nature of science (NOS), and science textbooks play a crucial role in the teaching of the nature of science (NOS). Understanding the nature of science is said to be effective when both understanding science concepts and doing science. Numerous studies focus on the teaching of NOS. This study investigates the effect of a science content that is prepared in history and philosophy of science (HPS) perspective on the NOSÃ‚Â understandings of pre-service science teachers. 34 sophomore pre-service science teachers participated in the study. The quasi-experimental method was used by employing a pre-test, an intervention, and a post-test which is the same as the pre-test. The intervention involved the presentation of science content from the HPS perspective in six weeks long of discussions. Data were collected through a survey that revealed categorical views regarding the characteristics of the NOS. The results showed that the demonstration of atom theories in the HPS perspective gave a positive effect on the pre-service science teachers in understanding the NOS.